Resilience-Oriented Distribution System Reconfiguration for Service Restoration Considering Distributed Generations - Wang, Peng (2017)
Significant evolution of distribution system, including distributed generation, microgrids and remote- controlled switches (RCSs), lead to novel and effective distribution system restoration (DSR) strategies. This paper proposes a resilience-oriented reconfiguration method to restore service to interrupted customers in distribution system as expeditious as possible after major blackouts. A structural model with virtual node and branches is provided to describe the radial structure constraint. The energy limits within microgrids are taken into considerations to account for scarcity of generation resources. The optimization problem is formulated as mixed-integer second- order cone programming (MISOCP), which employs a convex representation of a distribution network model on the basis of the conic quadratic format of the power flow equations. Case study is implemented on a modified 33-bus test system to verify the propose method.